Fault-related Rocks : A Photographic Atlas - Todd, Victoria R. (Victoria Roy); Tullis, Jan; Snoke, Arthur W. (Book collections on Project MUSE., 2014)
This is a richly illustrated reference book that provides a unique, comprehensive, and up-to-date survey of the rocks and structures of fault and shear zones. These zones are fundamental geologic structures in the Earth's crust. Their rigorous analysis is crucial to understanding the kinematics and dynamics of the continental and oceanic crust, the nature of earthquakes, and the formation of gold and hydrocarbon deposits. To document the variety of fault-related rocks, the book presents more than six hundred photographs of structures ranging in scale from outcrop to submicroscopic. These ar.